Pengaruh Penerapan Prinsip-Prinsip Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Kantor Desa Bina Baru Kecamatan Kulo Kabupaten Sidenreng Rappang - Habibi, Siti Nurhalima; Adnan, A. Astinah; Erfina, Erfina (Universitas Gajah Putih, 2025)
This study aims to determine the effect of service quality principles on community satisfaction at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency. This study uses a quantitative descriptive method with 47 respondents, using a saturated sampling technique. Data collection techniques through observation, questionnaires, and literature studies. The variables studied include the principles of strategic service quality s independent variables and community satisfaction as dependent variables. This study uses a simple linear regression analysis method with hypothesis testing through the IBM SPSS Version 21.00 for Windows application with a level of α = 0.05 as a form of data analysis process.The results of this study indicate that the variable of service quality principles (X) can be seen that the level of respondent achievement of 60.53% is categorized as less than good, therefore the principles of service quality must be further improved. Public Satisfaction (Y) with respondent achievement of 53.1%, so the t count value> t table, or 7.388> 2.014 then Ho is rejected and Ha is accepted, meaning significant. So, the influence of the application of service quality principles has a significant effect on public satisfaction at the Bina Baru Village Office, Kulo District, Sidenreng Rappang Regency.